International Humanitarian Law and Israel's Gazza Operation - Turhan, Turgut (Istanbul Univ, 2009)
This study deals with war crimes claimed to have been committed by Israel during Gazze operation. In this study firstly whether Israel's operation constitues a self defence or not has been discussed. Then the acts claimed to be committed are analysed by considering sources of humanitarion law. Finally the authority of the ICC to exercise jurisdiction over Israel is analysed. All considerations show that it is not possible to open an action againts officials of Israel in the ICC. But this situation does not terminate Israel's existing responsibility according to international customary law.
Keywords: Gazze operation; war crimes; international humanitarian law; International; Criminal Court; international armed conflicts.